Feasibility of fly ash as fluxing agent in mid- and low-grade phosphate rock carbothermal reduction and its reaction kinetics - Luo Biwei (De Gruyter, 2021)
The feasibility of industrial waste fly ash as an alternative fluxing agent for silica in carbothermal reduction of medium-low-grade phosphate ore was studied in this paper. With a series of single-factor experiments, the reduction rate of phosphate rock under different reaction temperature, reaction time, particle size, carbon excess coefficient, and silicon–calcium molar ratio was investigated with silica and fly ash as fluxing agents. Higher reduction rates were obtained with fly ash fluxing instead of silica. The optimal conditions were derived as: reaction temperature 1,300°C, reaction time 75 min, particle size 48–75 µm, carbon excess coefficient 1.2, and silicon–calcium molar ratio 1.2. The optimized process condition was verified with other two different phosphate rocks and it was proved universally. The apparent kinetics analyses demonstrated that the activation energy of fly ash fluxing is reduced by 31.57 kJ/mol as compared with that of silica. The mechanism of better fluxing effect by fly ash may be ascribed to the fact that the products formed within fly ash increase the amount of liquid phase in the reaction system and promote reduction reaction. Preliminary feasibility about the recycling of industrial waste fly ash in thermal phosphoric acid industry was elucidated in the paper.